MODERN INNOVATIVE TECHNOLOGIES IN AGRICULTURE: THE MAIN CHARACTERISTICS AND PROSPECTS OF IMPLEMENTATION - V. Bilinska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper analyzes the features of the latest technologies in agriculture. The basic challenges and opportunities of modern innovative technologies in all sectors of the agricultural sector are highlighted. The ways of overcoming the crisis of innovation and technological support of agricultural enterprises are suggested, which seeks to encourage dynamic development of agriculture Ukraine.